Current account deficits during heightened risk: Menacing or mitigating? - Kristin Forbes; Ida Hjortsoe; Tsvetelina Nenova (Bank of England, External Monetary Policy Committee Unit, 2016)
Large current account deficits, and the corresponding reliance on capital flows from abroad, can increase a country's vulnerability to periods of heightened risk and uncertainty. This paper develops a framework to evaluate such vulnerabilities. It highlights the central importance of two financial factors: income on international investments and changes in the valuations of those investments. We show how the characteristics of a country's international investment portfolio - the size of its international asset and liability holdings, their currency denominations, their split between equity and debt exposures, and their return characteristics - affect the dynamics of these financial factors. Then we decompose those dynamics into their drivers and explore how they are affected by domestic and global risk. We apply this framework to ten OECD economies, showing the flexibility of this approach and how the countries' different international investment portfolios generate different dynamics in international investment income and positions. These examples, including a more detailed assessment based on an SVAR for the United Kingdom, show that a substantial degree of international risk sharing can occur through current accounts and international portfolios. Our framework clarifies which characteristics of a country's international portfolio determine whether a current account deficit is "menacing" or "mitigating".
Keywords: F32; F21; F36; F42; 330; Current account; risk; international investment income; valuation effects